MORFOLOGI FUNGSIONAL KERANG BATIK Paphia undulata (Bivalvia: Veneridae) - Reni Ambarwati; Trijoko (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Veneridae bivalves are well-known and have economic significance, consumed as food and used for ornaments. Paphia undulata is one of the members of Veneridae. However, the functional morphology of this species has not been studied. The purpose of this research was to study the morphological characters of Phapia undulata. Specimens collected from Sidoarjo Coastal Water, Jawa Timur. Specimens relaxated by using MgCl2 7% in sea water and fixed in 10% formalin in sea water. Finally, specimens were preserved in 70% ethanol. Observation was done on the morphology internal of all specimens. Morphometric measurements were done on the length, height, and width of shells, length and width of ctenidium and labial palp. The results of this research showed that the diagnostic characters of P. undulata ornament of the shell, form and the type of siphon, and the form of foot. Ratio length: height of the shell = 1:0.6; ratio length = width of the shell: 1:0.4, ratio height: width of the shell = 1:0.6. Based on the morphometric measurements of ctenidium and labial palp, P. undulata can be categorized as suspension feeder. The ratio of ctenidium: labial palp = 5:1.